PERANCANGAN SISTEM PAKAR UNTUK MENDETEKSI PENYAKIT PADA TANAMAN CABE DENGAN METODE CERTAINTY FACTOR - Helmi Kurniawan; Iwan Fitrianto Rahmad (Universitas Raharja, 2012)
The Chilli in scientific language called Capsium annuum is not native to Indonesia, but came from the Americas, to be precise and South America Central America and Mexico. Quite a lot of chilli plants cultivated in Indonesia, especially in the land - the land of paddy fields and land - dry land that gets enough sunlight. In general, chilli plants grown as crops. Chilli and cultural communities, especially communities Medan Indonesia can hardly be separated, especially in cooking. Unlike the people - Europeans, Americans, and several Asian countries who prefer spicy pepper, Indonesian people especially people prefer spicy chili field. Virtually all the serving dishes found in cuisines that contain chilli although only slightly. Community needs for chili plants increases, along with the increasing growth of the community and increased social welfare. Although the need for chili plants increased, but not accompanied by increased production. As for the cause it can happen because ofpests, plant diseases, and less extension of the government. Artificial intelligence or artificial intelligence is a part of computer science that make the machine (computer) can do the job and as good as that done by humans. Intelligent systems (intelligent system) system wasbuilt using artificial intelligence techniques. One studied in artificial intelligence is the theory of certainty by using the theory of Certainty Factor (CF). Expert System (Expert System) is a knowledge-based programs that provide quality solutions to problems-problems of experts in a specific domain. Expert systems are computer programs that mimic the thought process and expert knowledge in solving a specific problem.